2015
DOI: 10.1021/nl503565t
|View full text |Cite|
|
Sign up to set email alerts
|

Nanovectorization of TRAIL with Single Wall Carbon Nanotubes Enhances Tumor Cell Killing

Abstract: Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL or Apo2L) is a member of the tumor necrosis factor (TNF) superfamily. This type II transmembrane protein is able to bound specifically to cancer cell receptors (i.e., TRAIL-R1 (or DR4) and TRAIL-R2 (or DR5)) and to induce apoptosis without being toxic for healthy cells. Because membrane-bound TRAIL induces stronger receptor aggregation and apoptosis than soluble TRAIL, we proposed here to vectorize TRAIL using single-walled carbon nanotubes (SWCNTs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 17 publications
3
77
0
1
Order By: Relevance
“…Statistical analyses were performed and showed that an amount of 80% of TRAIL coverage was obtained on most of SWCNT. This lead to increased efficiency of vectorized TRAIL compared to TRAIL alone [14].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Statistical analyses were performed and showed that an amount of 80% of TRAIL coverage was obtained on most of SWCNT. This lead to increased efficiency of vectorized TRAIL compared to TRAIL alone [14].…”
Section: Resultsmentioning
confidence: 99%
“…The detail of this synthesis is given elsewhere [14]. Briefly, purified SWCNT are cut in a 3:1 mixture of concentrated sulfuric and nitric acid (96% and 69% respectively), and sonicated in a water bath (Elmasonic model S30H, 50-60Hz, 280W) for 4h, and then vigorously stirred for 12h.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aslında sitotoksik ilaç-lar hızlı bir şekilde büyüyen ve bölünen hücrelere toksik şekilde etki edip hücreyi öldüren ya da fonksiyonunu durduran maddeler oldukları için tedavi amacıyla verilen sitotoksik ilacın etken maddesinin tümöre özgün olması ve diğer normal hücrelerde istenmeyen yan etkilerinin oluşmaması için farklı çözümler gelişti-rilmeye çalışılmaktadır. Günümüzde nanotaşıyıcılar terapötik etkinliğin ve güvenliğin geliştirilmesi bakı-mından umut vadetmektedir (23)(24)(25).…”
Section: Mezotelyoma Tedavi̇si̇unclassified
“…In recent years, the single-wall carbon nanotubes have attracted a great deal of attention because of the tubular structure, high specific surface, high thermal stability, and high chemical stability [2,3]. A large number of investigations have been carried out to research the significances and applications of these CNTs in many fields [4][5][6][7]. Adsorption and storage of gases, such as H 2 , are the most common applications of CNTs [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%